KINETICS OF EXPRESSION OF IMMUNOGLOBULIN A IN INTESTINAL EPITHELIUM OF NEWBORN ALPACA (Vicugna pacos) - Dionisio C., Juan (2014)
The objective of the present study was to determine and compare the levels of the relative expression of messenger RNA (mRNA) of IgA in intestinal epithelium of newborn alpaca up to 45 days old, that were in good health status (n=35) and ill with enteropathy (n=35). In each group, five animals were newborns before the consumption of colostrum and five for each week of age until the sixth week. Samples consisted in 2 cm length of jejunum, which was immediately preserved at -196 °C. The extraction was done with Trizol®, then complementary DNA (cDNA) was synthesized. Subsequently, the conventional PCR and real time RT-PCR was conducted using oligonucleotides designed for detecting the exon 1 of the Fc IgA region of alpaca. The quantification of the relative expression was made through normalization with the GAPDH gene mRNA and the relative expression calculations were conducted using the 2-ΔΔCt method. It was identified and demonstrated through the real time RT-PCR technique that alpacas encoded and transcribed mRNA of exon 1 of the IgA Fc region from the first day of age, but not at birth. Also, the relative expression is detected and produced in intestinal epithelium of newborn alpaca from one day of age, both in healthy and ill animals. Healthy animals have atendency of constant expression of mRNA of IgA until the fourth week of age, with slightly decrease in the subsequent weeks, whereas in enteric diseases IgA mRNA production is always superior than the expressed by the healthy animals, having significant differences (p<0.05) between the two groups (healthy 38.8 and sick 113 times respectively, with regard to the calibrator).